What should I study?: factors affecting student choice of subject at Libyan universities - Bait-Almal, Ali Ali Mohamed (2012)
This thesis focuses on the analysis and discussion of issues and factors influencing Libyan students’ subject choices at undergraduate level. It reviews the literature in the field, situating the study firmly in the context of educational research. However, it is noted that this literature has mainly emerged from Western contexts, and hence cultures. Nonetheless, the body of literature is used as a framework to analyse the Libyan case.